What drives the market for exchange-traded notes? - Rakowski, David; Shirley, Sara (Journal of Banking & Finance, 2020)
Exchange-traded notes (ETNs) are a relatively new form of security design that appear similar to exchange-traded funds (ETFs), but with no underlying portfolio holdings. We identify those characteristics of ETNs that are distinct from ETFs, and we test which ETN characteristics are most associated with interest from investors. We find that some ETNs have return patterns that are not spanned by ETFs, while other ETNs employ different strategies to attract investors. We show that the market activity for ETNs is associated with the distinctiveness of ETN returns, improvements in tracking errors, access to leverage, and the extent of risk transformation that ETNs allow.